# Question

Suppose f: Rn →Rn is differentiable and has a differentiable inverse F -1: Rn → Rn. Show that (f-1) I (a) = (fi (f-1(a)))-1.

## Answer to relevant Questions

Find the partial derivatives of the following functions: a. f(x,y,z)=xy b. f(x,y,z)=z c. f(x,y)=sin (xsin (y)) d. f(x,y,z)= sin (x sin (y sin(z))) e. f(x,y,z)=xy2 f. f(x,y,z)=xy=z g. f(x,y,z)=(x +y)2 h. f(x,y)= ...Let A= {x, y}: x Let f: R2 → R be defined as in Problem 1-26. Show that Dxf (0, 0) exists for all x, although f is not even continuous at (0,0).a. If f : R → R satisfies f1 (a) ≠ 0 for all a €R, show that f is 1-1 on all of R.Which non-objective piece is your favorite? Panel for Edwin Campbell (fig.32.16) or Malevich's Suprematist Composition (fig.32.17), or the Mondrian offerings (figs. 32.18 & 32.19).Post your question

0